2012
DOI: 10.1155/2012/726206
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Symptomatic for Boron Toxicity in Leaves of Tomato Plants

Abstract: The incidence of boron (B) toxicity has risen in areas of intensive agriculture close to the Mediterranean sea. The objective of this research was to study the how B toxicity (0.5 and 2 mM B) affects the time course of different indicators of abiotic stress in leaves of two tomato genotypes having different sensitivity to B toxicity (cv. Kosaco and cv. Josefina). Under the treatments of 0.5 and 2 mM B, the tomato plants showed a loss of biomass and foliar area. At the same time, in the leaves of both cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 50 publications
4
42
0
3
Order By: Relevance
“…In agreement with Nisar et al (2015), this pigment has an essential role in photoprotection, in which this protects the photosynthetic apparatus. These results corroborate the study of Cervilla et al (2012) when studied the B effect in Solanum lycopersicum plants and Danieli et al (2002) working with Diospyros kaki plants under high Ca.…”
Section: Ros Frequently Induces Increases In Elsupporting
confidence: 90%
“…In agreement with Nisar et al (2015), this pigment has an essential role in photoprotection, in which this protects the photosynthetic apparatus. These results corroborate the study of Cervilla et al (2012) when studied the B effect in Solanum lycopersicum plants and Danieli et al (2002) working with Diospyros kaki plants under high Ca.…”
Section: Ros Frequently Induces Increases In Elsupporting
confidence: 90%
“…Similarly, chlorophyls and carotenoids content decreased in leaves of Lolium perenne growing on the soil where fly ash was added (Lopareva-Pohu et al, 2011). Small content of chlorophylls and carotenoids in plant leaves indicates that the photosynthetic pigments are sensitive to stress factors that prevail on fly ash, such as high temperature, drought, toxic concentrations of As, B, Cd, Cr, Pb, and the small amount of Cu, Mn, and Zn in leaves (Hajibold and Amirazad, 2010;Cervilla et al, 2012;Gajić et al, 2016). However, displacement of Mg in the structure of chlorophyll molecule with toxic metal(loid) ions due to similar chemical properties reduces its activity and leads to the non-functional molecule (Van Assche and Clijsters, 1990).…”
Section: Plant Physiological Adaptation On Fly Ashmentioning
confidence: 99%
“…Therefore, a dominant-stress-factor model of Liebig-Sperngel might validate decreased growth rate of watermelon plants with increasing B dosages in the present work (Ben-Gal, Shani, 2002). Cervilla et al (2012) reported that a boron-sensitive tomato cultivar 'Josefina' showed a sharp decline in the biomass and leaf area on 10 days treatment of 0.5 mM B.…”
Section: Resultsmentioning
confidence: 54%